2013
DOI: 10.7567/jjap.52.122301
|View full text |Cite
|
Sign up to set email alerts
|

Mixing Effect of Gold and Silver Nanoparticles on Enhancement in Performance of Organic Thin-Film Solar Cells

Abstract: Bulk-heterojunction organic thin-film solar cells incorporating gold and silver nanoparticles were fabricated and evaluated. These nanoparticles were embedded in the hole-transport layer of the solar cells. Plasmonic absorption peaks of isolated gold and silver nanoparticles were confirmed from extinction spectra even in the hole-transport material. The incorporation of gold and silver nanoparticles increased the photoelectric conversion efficiency of organic thin-film solar cells, whose enhancement ratio was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…12) In the case of the AuNP or AgNP solutions, a 20 wt% of concentrated AuNPs or AgNPs solution was mixed with an aqueous solution of PEDOT:PSS, acting as the hole-transport material. In the case when a mixture of AuNPs, AgNPs, and PEDOT:PSS was used, a 20 wt% concentrated mixed solution of AuNPs and AgNPs (AuNPs:AgNPs = 1:1) was mixed with the PEDOT:PSS solution.…”
Section: Methodsmentioning
confidence: 99%
“…12) In the case of the AuNP or AgNP solutions, a 20 wt% of concentrated AuNPs or AgNPs solution was mixed with an aqueous solution of PEDOT:PSS, acting as the hole-transport material. In the case when a mixture of AuNPs, AgNPs, and PEDOT:PSS was used, a 20 wt% concentrated mixed solution of AuNPs and AgNPs (AuNPs:AgNPs = 1:1) was mixed with the PEDOT:PSS solution.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, noble metal nanoparticles are expected to contribute to the enhancement of the photoelectric conversion efficiency in organic thin‐film solar cells. Indeed, many studies have reported that organic thin‐film solar cells with gold or silver nanoparticles have enhanced photoelectric conversion efficiencies , even in the inverted‐type organic thin‐film solar cells .…”
Section: Introductionmentioning
confidence: 99%
“…While, in the case of AuNPs(100): AgNPs(0)/PEI/Glass, no rod-shaped particles was observed. 35,36) Relative atomic concentration ratios of gold and silver were estimated from EDX analysis of AuNPs(m):AgNPs(n)/ PEI/ITO (m:n = 0:100, 25:75, 50:50, 75:25, and 100:0), which are summarized in Table I. Order of the ratios of gold and silver elements are corresponding to the mixing volume ratios of AuNPs and AgNPs colloidal solutions for fabrication of the modified substrates.…”
mentioning
confidence: 99%